Getting to center : pathways to finding yourself within the great unknown - Grace, Marlee (William Morrow, 2020)
Picking up where How to Not Always Be Working left off, Getting to Center is an empathetic offering to those who are looking for a roadmap for finding their way back to equilibrium. This book meditates on endings, grief and joy, ease, hope, addiction, and beginnings, pairing Marlee's own experiences and wisdom with practical exercises and tools for creating balance and understanding within the natural changes of life.